PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TAI TERHADAPHASIL BELAJAR IPS KELAS V SDN 24 PONTIANAK TENGGARA - Zamiril, Zamiril; Marli, Suhardi; Kresnadi, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this study is to describe the effect of the TAI type of cooperative learning model on social studies learning outcomes in the 5th grade of SDN 24 Pontianak Tenggara. The research method used was an experiment in the form of Quasy Experiment Designs. The population of this study were all 5th grade students of SDN 24 Pontianak Tenggara, totaling 60 students. The sample of this study was simple random sampling, is 30 students of VA as the control class and 30 students of VB as the experimental class. Data collection techniques use measurement techniques. The instrument used was a multiple choice test of 40 questions.Based on the calculation obtained by the average post-test learning outcomes of the control class 72,83 and the average post-test learning outcomes of the experimental class 79,83 so that it obtained t count post-test data of 1,949 with t table for the significance level Î± = 5 % and dk = 58 of 1,672. Because t count> t table, then Ha is accepted. So, so, the application of the TAI type cooperative model affects to learning outcomes of social science in the 5th grade of SDN 24 Pontianak Tenggara. Calculation of effect size was obtained at 0,51 (medium), so that the application of the TAI type cooperative model had an effect on the Social Studies learning outcomes in the 5th grade of SDN 24 Pontianak Tenggara.Â Keywords: Cooperative learning type TAI, Learning Achievement, Social Studies